Assessment of Nutritional Knowledge of Nurses Regarding Diet in Some Diseases - Talukdar, Pallavi; Sarmah, Juliana (Indian Journal of Extension Education, 2012)
The present study was conducted to assess the existing knowledge of nurses on nutrition along with some background  characteristics. One hundred and twenty nurses from three government hospitals and three private hospitals of three  different districts were administered a questionnaire comprising questions related to nutrition. Half of the total  respondents (50%) belonged to young age group (20-30 years), 49.2 per cent had diploma in nursing and 49.1 per cent had  %1-5 years of professional experience. Majority (91 ) of the respondents had medium level of mass media exposure.  Around 61.7 per cent had medium level of nutritional knowledge. There was a need for increasing the nutritional  knowledge of nurses. Proper training on nutrition education should be conducted frequently.
Keywords: Nutrition; nurses; knowledge; diseases